MHC haplotype and B cell autoimmunity: Correlation with pathogenic IgG autoantibody subclasses and Fc glycosylation patterns. Issue 2 (22nd October 2021) - Nogueira Almeida, Larissa; Clauder, Ann‐Katrin; Meng, Lingzhang; Ehlers, Marc; Arce, Sergio; Manz, Rudolf Armin
Abstract: Genome‐wide association studies (GWAS) have identified many genes that are associated with the development of certain autoimmune disorders, but the MHC haplotypes still represent the most prevalent genetic risk factor for many autoimmune diseases. The mechanisms by which MHC‐associated genetic susceptibility translates into B cell autoimmunity and the development of autoimmune diseases are complex. There is increasing evidence that the MHC haplotype modulates autoreactive B cell responses in multiple ways. Instead of merely inhibiting the production of IgG autoantibodies and mediating complete immunological tolerance, the non‐permitting MHC haplotypes seem to facilitate the production of IgG autoantibodies exhibiting Fc glycosylation patterns that are associated with reduced pathogenicity and a protective cytokine profile of T follicular helper (Tfh) cells. Here, we discuss mechanisms linking MHC haplotypes to the production of pathogenic IgG autoantibodies, which could be relevant for the development of improved diagnosis, particularly in the context of individual medicine. Abstract : MHC modulates T cell tolerance and differentiation of autoreactive Tfh cells into distinct helper cell populations, eventually affecting the quantity of autoantibodies, their isotypes, and pro‐ or anti‐inflammatory Fc glycosylation patterns. Disease permitting MHC haplotypes support the formation of autoantibodies of inflammation‐promoting IgG subclasses, presenting low Fc N‐glycosylation patterns with increased pathogenic potential.